PEMBERDAYAAN MASYARAKAT DALAM MENGEMBANGKAN EKONOMI LOKAL BERWAWASAN LINGKUNGAN DI DESA NGRANCAH KECAMATAN GRABAG KABUPATEN MAGELANG - Tajuddin, Iqbal; Aji, Ananto; Setyaningsih, Wahyu (Badan Pengembang Konservasi UNNES, 2018)
The purposes of the research, 1) to know the impact of the community empowerment activities toward the local economic development using environment insight, 2) to analize the impacts of local economic development using environmental insight. The population are the village farmers who are the members of farmer groups consisted of 252 people. 20% or 50 samples were taken using proportional random sampling. The data collection techniques used were questionnaires, observations, interviews and documentations. The technique analysis used were descriptive analysis and multiple regression analysis. The result of research showed that there is simultaneously contribution between community empowerment to local economic development with environment insight that is equal to 58,3%. The impact of local economic development on the environment to the community, increasing income, expanding of employment opportunities, reducing landslides and increasing the number of water springs. It can be concluded that there is a positive correlation between the empowerment of the community towards the local economic development using environment insight business in Ngrancah Village.